Evaluation Report 1954 - Planning Commission (Planning Commission, 1954)
As the need for augmenting agricultural production was acute when the community project programme was conceived there was a general expectation that areas which held promise of quick betterment, by way of improving water supply, reclamation of land etc., would be selected for the initial introduction of the scheme. This has been done in some cases. On the other hand, in most States some areas were selected for exactly the opposite reason, namely their general economic backwardness. Large populations, low yields, scarcity of water, irregular rainfall, uncertain climate, tribal populations— these and similar factors indicated the need for special attention. As the community projects were the newly approved pattern of rural development, it was natural to extend it from the promising to the needy areas. In due course, almost all areas began to press their representatives in the State governments to have them included in the scheme of intensive development. A phased programme of community projects and national extension blocks was, therefore, worked out for all the villages, and has now been adopted. This development is in keeping with the needs of a country-wide movement towards a progressive transformation of rural life and business. Local circumstances in respect of resources, participation and leadership are, however, so variable that the actual results are bound to differ, both in absolute quantity and proportionately to the effort.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation, Planning Commission, Government of India